Effect of analgesic treatments on voluntary activity, mechanical sensitivity and muscle regeneration after cardiotoxin injection in mice - Charline Jomard; Natacha Boyer; Aurélie Fessard; Bénédicte Chazaud; Julien Gondin (Scientific Reports)
Abstract Cardiotoxin injection is a commonly used method to induce muscle damage for studying skeletal muscle regeneration. Toxic injuries cause extensive myofiber damage and necrosis, leading to widespread muscle injury. This model results in an important macrophage infiltration, the release of chemical mediators and the activation of nociceptors, which may result in muscle pain. Managing pain in animal research is critical from both an ethical and scientific perspectives. The goal of this study was to evaluate whether two widely used analgesics, paracetamol and buprenorphine, affect mouse locomotor activity, mechanical sensitivity and muscle regeneration following cardiotoxin injection. Pain was assessed through the Von Frey test and voluntary wheel-running activity recordings. In parallel, we quantified histological and cellular markers of muscle regeneration and assessed the inflammatory response using flow cytometry. Although buprenorphine alleviated stimulus-evoked pain behaviors, none of the analgesics minimized cardiotoxin-induced reduction in wheel-running activity nor affected muscle regeneration and the inflammatory response following injury. Both paracetamol and buprenorphine may even negatively impact spontaneous activity. These findings demonstrate that cardiotoxin-induced muscle injury markedly impairs spontaneous locomotor activity, an effect that may be further amplified by the administration of analgesics. Our findings raise questions about the effectiveness of these pharmacological approaches in pain management after muscle injury, particularly when administrated within the first 24 h post-injury.